Proposta de método para monitoramento e controle de projetos utilizando análise multicritério - MCDA-C - Bassani, Bia Cristina (2021)
Project management is taking a prominent position in organizations of different sizes and segments, however, managing only the term, cost and scope of a project, as planned, is not enough to guarantee project success. In addition, it is clear that there is no single way for project managers to analyze decisions, not even the situation in which they find themselves. And it is a fact that several organizations have problems in the monitoring and control process of their projects, as they have several points that need to be monitored, depending on the situation, changed, with no quantitative and analytical method that clearly presented the critical and positive points of your phase. It was found that project monitoring and control has nine processes that need to be monitored simultaneously in order to obtain the best possible performance and achieve project success. In this bias, this study aimed to develop a proposed method for monitoring and controlling projects using the Constructivist Decision Support Multicriteria Methodology - MCDA-C. The new method was applied in a Research Center that develops projects focused on technologies, energy generation and regional development. The research methodology was a case study, in an in-depth and analytical way, with the specific objectives: identifying and defining project management criteria that are related to the monitoring and control process; to develop a model, using the Constructivist Decision Support Multicriteria Methodology – MCDA-C according to the project management criteria; apply the proposed method and carry out the analysis and discussion of the results. The study resulted in important data for stakeholders to monitor and control the progress of projects, strengthening their relationships and prospecting for new projects with graphic data in a quantitative and objective way. It can also be seen that the new method brought better control of the project monitoring and control process, monitoring data history and helping to identify critical points, supporting those responsible with information that contribute to their decisions.